Efficient degradation of tetrabromobisphenol A by synergistic integration of Fe/Ni bimetallic catalysis and microbial acclimation. (1st October 2017) - Peng, Xingxing; Wang, Zhangna; Huang, Jingfei; Pittendrigh, Barry R.; Liu, Shengwei; Jia, Xiaoshan; Wong, Po Keung
Abstract: This study provides a novel technology for the degradation of tetrabromobisphenol A (TBBPA) via an interaction of Fe redox and a shift of functional microbial community. TBBPA was degraded by integration of synthesized Fe-Ni bimetallic particles and enriched microbial consortium within an aqueous system. This cooperative integration yielded the best TBBPA-degrading capacity (100% removal after treatment for 2 h) and highest TOC-removing efficiency (94.5% removal after treatment for 96 h), as well as the lowest toxicity to Vibrio fischeri (almost 0% growth inhibition during reaction). The synergistic mechanism of integrated system was clarified based on systematical analyses of the degradation processes as well as the shifts in microbial community. Owing to the microbial metabolism and the Fenton-like process of leaked Fe 2+, Fe 3+ and Ni 2+ from Fe-Ni bimetallic catalyst, reactive oxidative species (ROS), including superoxide (O2 − ), hydroxyl radicals (OH) and hydrogen peroxide (H2 O2 ) were produced and evaluated by multiple techniques. Moreover, the quenching experiments indicated that OH was the major ROS leading to TBBPA degradation, rather than H2 O2 or O2 − . Based on the analysis of the 12 detected intermediates, three parallel pathways were proposed. It was clearly revealed that reductive and oxidative debromination, hydroxylation, and β-scission simultaneously occurred in the integrated system. Fe non-randomly accelerated the enrichment of TBBPA-degrading microbes (e.g. Pseudomonas sp. and Citrobacter sp., etc.). Above all, this novel technology has great promise for field-applications for remediation of TBBPA-contaminated field. Graphical abstract: Highlights: Integrating Fe-Ni bimetallic and enriched microbial units to degrade TBBPA. Enhanced TBBPA degradation by the integrated system. The Fe-Ni bimetallic catalyst was characterized by standard analyses. OH involved in TBBPA degradation by the integrated system. Microbial community shift was analyzed by high through-put sequencing.